2019
DOI: 10.3390/ani9090678
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Rat Grimace Scale to Evaluate Visceral Pain in a Model of Chemotherapy-Induced Mucositis

Abstract: Simple SummaryMucositis is a painful and often debilitating condition associated with cancer treatment. Management of associated symptoms is an important clinical consideration. Animal models are used in mucositis research to model the condition in humans in order to develop novel therapeutic agents to relieve symptoms. Previous animal studies have focused on disease severity and outcomes, but often failed to measure pain. The rat grimace scale (RGS) is a validated observational measure used to gauge pain leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Infection is the most common complication for patients with HM treated with chemotherapy 19 , 27 , and is a predictor for adverse outcomes. The most severe infections in these patients are BSIs, probably because of bone marrow suppression, neutropenia 28 and mucosal injury induced by chemotherapy 29 . The frequency of BSIs was 24.1% in this study, which is much higher than our previously reported for pre-engraftment patients in Ren et al (18.3%) 30 or reported for neutropenic patients in Wisplinghoff et al (14.3%) 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Infection is the most common complication for patients with HM treated with chemotherapy 19 , 27 , and is a predictor for adverse outcomes. The most severe infections in these patients are BSIs, probably because of bone marrow suppression, neutropenia 28 and mucosal injury induced by chemotherapy 29 . The frequency of BSIs was 24.1% in this study, which is much higher than our previously reported for pre-engraftment patients in Ren et al (18.3%) 30 or reported for neutropenic patients in Wisplinghoff et al (14.3%) 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of this validation work has occurred in rodent models. It is beyond the scope of this review to describe all of the models used but the range includes oncology (see e.g., [ 47 , 48 , 49 , 50 ]), infectious disease [ 51 ], pain models [ 48 , 52 , 53 ], neurological conditions [ 33 , 54 , 55 ], genetic conditions [ 56 ], and maxillofacial interventions [ 49 , 50 , 57 ]. However, the vast majority of research to date has performed grimace scoring retrospectively from captured video footage.…”
Section: Clinical Applicability Of Grimace Scales In Biomedical Rementioning
confidence: 99%
“…However, there was some investigation of a range of technologies which minimize the time taken for various aspects of this process. At the simplest level use of freeware video to JPG converter software can reduce the time associated with manual searching and capture of images from recorded video footage by automating the capture process [ 48 ]. However, this still requires manual viewing of the selected images to obtain unobstructed head shots.…”
Section: Clinical Applicability Of Grimace Scales In Biomedical Rementioning
confidence: 99%
“…It is beyond the scope of this review to describe all of the models used but the range includes oncology (see e.g. [47][48][49][50] ), infectious disease 51 , pain models 48,52,53 , neurological conditions 33,54,55 , genetic conditions 56 , and maxillofacial interventions 49,50,57 . However, the vast majority of research to date has performed grimace scoring retrospectively from captured video footage.…”
Section: Development Of Real-time Grimace Scoresmentioning
confidence: 99%
“…However, there has been investigation of a range of technologies which minimize the time taken for various aspects of this process. At the simplest level use of freeware video to JPG converter software can reduce the time associated with manual searching and capture of images from recorded video footage by automating the capture process 48 . However, this still requires manual viewing of the selected images to obtain unobstructed head shots.…”
Section: Automation Of Techniquesmentioning
confidence: 99%